The AST/ALT (De Ritis) ratio predicts clinical outcome in patients with pancreatic cancer treated with first-line nab-paclitaxel and gemcitabine: post hoc analysis of an Austrian multicenter, noninterventional study. (April 2020) - Riedl, Jakob Michael; Posch, Florian; Prager, Gerald; Eisterer, Wolfgang; Oehler, Leopold; Sliwa, Thamer; Wilthoner, Klaus; Petzer, Andreas; Pichler, Petra; Hubmann, Eva; Winder, Thomas; Burgstaller, Sonja; et al.
Background: The pretreatment De Ritis ratio [aspartate transaminase (AST)/alanine transaminase (ALT)] has been shown to be an adverse prognostic marker in various cancer entities. However, its relevance to advanced pancreatic ductal adenocarcinoma (PDAC) has not yet been studied. In the present study we investigated the AST/ALT ratio as a possible predictor of treatment response and disease outcome in patients with advanced PDAC treated with first-line gemcitabine/nab-paclitaxel. Methods: A post hoc analysis of a prospective, multicenter, noninterventional study was performed. A total of 202 patients with advanced PDAC treated with first-line gemcitabine/nab-paclitaxel for whom the AST/ALT ratio was measured were included in this analysis. Results: Median and 1-year progression-free survival estimates were 4.8 months and 5.1%, respectively in patients with an AST/ALT ratio above the 75th percentile of its distribution, and 6.0 months and 18.7%, respectively in patients with an AST/ALT ratio less than or equal to this cutoff, respectively (log-rank p = 0.004). In univariable Cox regression, a doubling of the AST/ALT ratio was associated with a 1.4-fold higher relative risk of progression or death [hazard ratio = 1.38, 95% confidence interval (CI): 1.06–1.80, p = 0.017]. The prognostic association was also found in multivariable analysis adjusting for Eastern Cooperative Oncology Group performance status and lung metastases (hazard ratio per AST/ALT ratio doubling = 1.32, 95% CI: 1.00–1.75, p = 0.047). In treatment response analysis, a doubling of the AST/ALT ratio was associated with a 0.5-fold lower odds of objective response (odds ratio = 0.54, 95% CI: 0.31–0.94, p = 0.020). Conclusions: The pretreatment serum AST/ALT ratio predicts poor disease outcome and response rate in patients with advanced PDAC treated with gemcitabine/nab-paclitaxel and might represent a novel and inexpensive marker for individual risk assessment in the treatment of pancreatic cancer.